ELECTROMAGNETIC ENVIRONMENT IN CITIES AND RESIDENTIAL AREAS: ELECTROMAGNETIC ENVIRONMENT IN CITIES AND RESIDENTIAL AREAS - Vasilev , Dragomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper presents Electromagnetic Environment in cities. It noted that in the field of living hygiene, the concept of "risk" and safety of life is not sufficiently developed. This situation is preserved to this day, which creates real preconditions for the formation of unfavorable living conditions with damage to the health of the population. It was not until 1996 that the first hygiene standards for EMF levels were used when using consumer goods at home.